Rekonstruksi konsep fakir dan miskin sebagai mustahik zakat - Dede Rodin (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
Among asnaf are entitled to receive zakat is faqir and miskin, but both groups are often interpretedoverlap.This article aims to reconstruct the concept of faqir and miskin with perspective of the Qur’an.This is because that, in addition to the Qur’an is believed by Muslims as the main source of law, also theconcept of faqir and miskin as well as ‘illat that causes both as mustahik zakat will make the distributionof zakat in accordance with its objectives. The study of the verses of the Qur’an about the faqir andmiskin, results the conclusions: First, faqir is who are deterred from livelihoold as work reason or udhur.The work reason is due to religious activity or work shar’i as da’wah and jihad. While the udhur reasoncaused by kauni destiny like a disability, palsied, and old. Thus, ‘illat for faqr groups derived from God’sglory and the exam so that they get the respect, zakat and other compensation. The glory reason comingfrom the work shar’iyyah, while the test reason comes from udhur kauniyyah. While the miskin are literallymeans sakana; silent and not moving, that miskin terms describe the result of a weak state of a personbecause he chose sakana lifestyle (silent, static, not developing skills in his life). As a result he becamepoor and do not have anything whatsoever to fulfill their needs.